Synthesis, Crystal Structure, Spectroscopic and Computational Studies of a New Organic Crystal: Quinoxaline: 3,5-Dichloro-2-hydroxybenzoic Acid - Kohila, C.; Kumar, G. Dinesh; Kavitha, G.; Jyothi, S. (Asian Journal of Chemistry, 2026)
A new molecular cocrystal of quinoxaline with 3,5-dichloro-2-hydroxybenzoic acid (QODCS) was synthesised by slow evaporation technique and its structural, spectral, thermal and nonlinear optical properties were studied. Single crystal X-ray diffraction revealed that the crystal belongs to the triclinic system with P-1 space group and is stabilised by hydrogen bonding and π···π interactions. FT-IR and UV–Vis analyses confirmed the formation of the cocrystal and the presence of conjugated systems. Thermal analysis showed that the material is stable up to 286 ºC with single-stage decomposition. Hirshfeld surface and NBO analyses indicated strong intermolecular interactions and effective charge transfer within the system. Theoretical UV studies supported π-electron delocalisation through HOMO–LUMO transitions. The crystal exhibited enhanced dipole moment and significant hyperpolarizability values, indicating strong nonlinear optical behaviour.